TIME EXTENSIONS OF PETRI NETS FOR MODELLING AND YERIFICATION OF HARD REAL-TIME SYSTEMS - Samolej, Slawomir; Szmuc, Tomasz (Computer Science, 2020)
The main aim ofthepaper is apresentation oftime extensions ofPetri nets appropriate for modelling and analysis o f hard real-time systems. It is assumed, that the extensions must provide a model o f time flow, an ability to force a transition to fire within a stated timing constraint (the so-called the strongfiring rule), and timing constraints represented by inte- rvals. The presented survey includes extensions o f classical Place/Transition Petri nets, as well as the ones applied to high-level Petri nets. An expressiveness o f each time extension is illustrated using simple hard real-time system. The paper includes also a brief description o f analysis and verification methods related to the extensions, and a survey o f software tools supporting modelling and analysis o f the considered Petri nets.